2020 42nd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2020
DOI: 10.1109/embc44109.2020.9175335
|View full text |Cite
|
Sign up to set email alerts
|

Selective Wireless Stimulation of Rat Sciatic Nerve

Abstract: Chronic stability of functional performance is a significant challenge to the success of implantable devices for neural stimulation and recording. Integrating wireless technology with typical microelectrode array designs is one approach that may reduce instances of mechanical failure and improve the long-term performance of neural devices. We have investigated the long-term stability of Wireless Floating Microelectrode Arrays (WMFAs) implanted in rat sciatic nerve, and their ability to selectively recruit musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The remaining 10 electrodes in the group of 21 electrodes evoked a motor response sporadically over the 38 week study and at current thresholds typically above 40 µA. We observed consistent motor recruitment patterns over a 38 week study period at thresholds ranging from 4.1 µA (0.8 nC ph −1 , 41 µC cm −2 ) to 2,3,4,5,6,7,8,10,12,14,16,18,20,22,24,26,28,30,32,34,36,38). For animal A01, no data was recorded during week 7, and no data was recorded for electrode 10 at any time point as the electrode was determined to be non-functional at the time of device fabrication.…”
Section: Response To Stimulationsupporting
confidence: 62%
See 2 more Smart Citations
“…The remaining 10 electrodes in the group of 21 electrodes evoked a motor response sporadically over the 38 week study and at current thresholds typically above 40 µA. We observed consistent motor recruitment patterns over a 38 week study period at thresholds ranging from 4.1 µA (0.8 nC ph −1 , 41 µC cm −2 ) to 2,3,4,5,6,7,8,10,12,14,16,18,20,22,24,26,28,30,32,34,36,38). For animal A01, no data was recorded during week 7, and no data was recorded for electrode 10 at any time point as the electrode was determined to be non-functional at the time of device fabrication.…”
Section: Response To Stimulationsupporting
confidence: 62%
“…Partial data from weeks 1 through 8 of this study were also reported in [24]. Of the 96 electrodes implanted in total (16 electrodes per device in n = 6 animals), 21 appeared to be either within the epineurium or outside the nerve upon visual inspection at the time of implantation (A01, A03, and A05-E14, E15, and E16; A02, A04, and A06-E01, E02, E03, and E04).…”
Section: Response To Stimulationmentioning
confidence: 82%
See 1 more Smart Citation
“…2 Video tracking of limb motion can be used to distinguish between plantarflexion and dorsiflexion as well as individual toe movements. 134,135 The most quantifiable test method however is electrical measurement of the evoked muscle response, called electromyography (EMG). 136 EMG measures the action potentials of muscle fibers during muscle contractions.…”
Section: Quantifying Nerve Stimulationmentioning
confidence: 99%
“…For this, the back-end connection would need to be replaced with a non-contact method for transmission of power and information. Some non-stretchable PNIs 93,134,137 , see Chapter 3.3, as well as other stretchable electronic implants not intended for the PNS 138 , already employ such an approach, and one could build on their acquired knowledge. The most promising power transfer methods are radiofrequency (RF) and light.…”
mentioning
confidence: 99%